Change in Fluid and Crystallized Intelligence and Student Achievement: The Role of Intellectual Engagement. Issue 4 (28th March 2017) - Hülür, Gizem; Gasimova, Fidan; Robitzsch, Alexander; Wilhelm, Oliver
Abstract : Intellectual engagement (IE) refers to enjoyment of intellectual activities and is proposed as causal for knowledge acquisition. The role of IE for cognitive development was examined utilizing 2‐year longitudinal data from 112 ninth graders (average baseline age: 14.7 years). Higher baseline IE predicted higher baseline crystallized ability but not changes therein, and was not associated with fluid ability. Furthermore, IE predicted change in school grades in language but not in mathematics grades or in standardized tests. These findings suggest that IE is not a major predictor of knowledge acquisition in adolescence, where degree of self‐determination in intellectual behaviors may be relatively limited. Open questions for future research are addressed, including reciprocal longitudinal associations between IE and academic and cognitive development.